2008
DOI: 10.3171/jns/2008/109/8/0215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a collagen matrix for cranial and spinal dural reconstruction using different fixation techniques

Abstract: The collagen matrix is an effective and safe cranial and spinal dural substitute that can be used even in cases of an existing local infection. Postoperative deep infection increases the risk for CSF leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 31 publications
(24 reference statements)
4
48
1
3
Order By: Relevance
“…Reported benefits include a microstructure that has been optimized for fibroblast and blood vessel ingrowth, rapid incorporation into surrounding tissue, and minimal inflammatory reaction in the surrounding native tissue. [26][27][28][29] Studies have been published showing the efficacy of all the materials mentioned herein, but there continues to be a paucity of comparative evidence supporting one material over another. To date, the literature has defined success with a single outcome: repair with no recurrence of CSF leak.…”
Section: Resultsmentioning
confidence: 99%
“…Reported benefits include a microstructure that has been optimized for fibroblast and blood vessel ingrowth, rapid incorporation into surrounding tissue, and minimal inflammatory reaction in the surrounding native tissue. [26][27][28][29] Studies have been published showing the efficacy of all the materials mentioned herein, but there continues to be a paucity of comparative evidence supporting one material over another. To date, the literature has defined success with a single outcome: repair with no recurrence of CSF leak.…”
Section: Resultsmentioning
confidence: 99%
“…Other Authors demonstrate an average infection rate of 4,5% using porous collagen matrix (Gnanalingham et al, 2002). Collagen matrix is used to obtain a watertight dural closure (Stendel et al, 2008); they report an average infection rate of 2,6%, an average cerebrospinal fluid leakage rate of 5,2% and an average cerebrospinal fluid fistula of 2,6%. Comparing this data with those obtained from literature, they have demonstrated that the use of collagen matrix determines a lower risk of infection and cerebrospinal fluid loss than the use of autograft or synthetic material.…”
Section: Complications Of Duraplastiesmentioning
confidence: 99%
“…If the overlap between the graft and the dura is appropriate (minimum overlap required = 1 cm), collagen matrix can be used as an onlay graft without an additional fixation; otherwise neurosurgeon needs to use one or multiple additional fixation (for example, fibrin sealant). However, it seems that simultaneous multiple fixation are associated with a higher rate of infection and cerebrospinal fluid leaks (Stendel et al, 2008).…”
Section: Xenograftsmentioning
confidence: 99%
“…Acellular human dermis grafts have the advantage of requiring no additional surgical incision, being relatively cheap, and being relatively easy to use, but there are reports of atrophy or decreased adhesion with the brain surface [6]. Engineered collagen grafts (i.e., DuraGen; Integra Neurosciences, Plainsboro, NJ, USA), thought to serve as a scaffolding for indigenous cell growth, can be applied in a sutureless method, but may predispose the patient to postoperative complications and increase the cost of surgery [7].…”
Section: Introductionmentioning
confidence: 99%